1998
DOI: 10.1359/jbmr.1998.13.10.1569
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Polymorphism of the Transforming Growth Factor-β1 Gene with Genetic Susceptibility to Osteoporosis in Postmenopausal Japanese Women

Abstract: Transforming growth factor-␤ (TGF-␤) is both abundant in bone and an important regulator of bone metabolism. A T3 C transition at nucleotide 29 in the signal sequence region of the TGF-␤1 gene results in a Leu3 Pro substitution at amino acid position 10. The possible association of this polymorphism with bone mass and the prevalence of osteoporosis has now been investigated in a total of 287 postmenopausal women from two regions (Obu City, Aichi Prefecture, and Sanda City, Hyogo Prefecture) of Japan. A signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
100
3
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 310 publications
(115 citation statements)
references
References 33 publications
9
100
3
3
Order By: Relevance
“…This result is consistent with many previous studies, which report the association between the T869C polymorphism, the C-509T polymorphism of the TGF-β1 gene and serum TGF-β1 level, and BMD (Langdahl et al, 1997;Yamada et al, 1998Yamada et al, , 2001). The first report by Yamada et al (1998) stated that there was association between the CC genotype of the T869C polymorphism and higher serum TGF-β1 level, and higher BMD at lumbar spine, observed in postmenopausal Japanese women.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is consistent with many previous studies, which report the association between the T869C polymorphism, the C-509T polymorphism of the TGF-β1 gene and serum TGF-β1 level, and BMD (Langdahl et al, 1997;Yamada et al, 1998Yamada et al, , 2001). The first report by Yamada et al (1998) stated that there was association between the CC genotype of the T869C polymorphism and higher serum TGF-β1 level, and higher BMD at lumbar spine, observed in postmenopausal Japanese women.…”
Section: Discussionsupporting
confidence: 93%
“…The first report by Yamada et al (1998) stated that there was association between the CC genotype of the T869C polymorphism and higher serum TGF-β1 level, and higher BMD at lumbar spine, observed in postmenopausal Japanese women. Hinke et al (2001) showed the TT genotype of this polymorphism was associated with a higher serum TGF-β1 level, higher BMD at the lumbar spine, and the femoral neck in postmenopausal German women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five polymorphisms in white populations have been identified: 2 in the promoter region at positions -800 and -509, 1 at position +72 in a non-translated region, and 2 in the signal sequence at positions +869 and +915. Among these polymorphisms, -C509T is reportedly associated with some clinical phenotypes (Awad et al, 1998;Baan et al, 2000;Yokota et al, 2000;Yamada et al, 1998Yamada et al, , 2001Lacha et al, 2001). Grainger et al (1999) have found that the C-509T polymorphism is associated with the circulating concentration of TGF-β1, which is significantly lower in white women with the CC genotype compared with that in subjects with other genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The C-509T polymorphism, in homozygosis, was associated with low levels of circulating TGF-β 1 concentration, when compared with other genotypes, in white women and in the Indian population. 3 On the other hand, the CC genotype of T869C polymorphism was related to a high concentration of TGF-β 1 in Japanese individuals, 40 but not in white individuals. 41 In another study, Li et al 8 verified that the C-509T and T869C polymorphisms increased risk of asthma and atopy in Mexican children.…”
Section: Discussionmentioning
confidence: 97%